18th Annual Meeting of the Safety Pharmacology Society: drug safety assessment on gastrointestinal system functions. Issue 1 (2nd January 2020) - Cavero, Icilio; Holzgrefe, Henry H.
ABSTRACT: Introduction : The 18 th Annual Meeting of the Safety Pharmacology Society included a session dedicated to the assessment of drug safety on the gastrointestinal (GI) system. Areas covered : GI anatomy, physiology, adverse effects (AEs) of chemical and biological therapies, and approaches to mitigate them. Expert opinion : GI AEs, albeit common and generally of minor intensity, may prolong clinical development time and reduce patient compliance.